Characteristics of Iraqi journalism from the Ottoman period to the beginning of the Third Republic - رەسوڵ, بەهرۆز عەلی (Sulaimani Journal for Humanities, 2019)
The history of journalism in iraq dates back to the end of the Ottman empires rule.It has progressed in a number of stages. Each stage has its own characteristics and played a specific function that was reflective of the political system of the period. This present study examines the beginning of the journalism in iraqe and show that it coincides with the creation of Iraq as a monarchy. At the time state,private and partisan newspapers were published. Journalism thrived in the period compared to the preceding period . After the revolution of 1958, in which the monaachical system was overthrown and a republic was declared ,the press became the language of the revolution. Its function was to raise awareness in matters related to the revolution.it terms of ownership, journalism in Iraq was owned by the state and only government newspapers were in circulation.In this stage, the press was used for propaganda purposes and the spread of the ideology of the regime. In the aftermath of the toppling of Saddam Hussen and the baath Regime in 2003 , journalism grew and ownership was diversified and state , private and partisan publication with various sectarian,nationalistic, personal, and collective orientations began publication. The freedom of press grew and the press could influence public opinion. That said, the press had a negative side because it became a part of the ongoing conflict and the political arena in Iraq.Its role was neagative in that it partly caused the spread of sectarian violence from the political elite to the public. Concerning Kurdish journalism,its beginning and growth, within the history of journalism in Iraq,this study shows that Kurdish journalism began under British rule of Iraq. Journalism thrived during the monarchy rule with the publication of state. Private and independent newspapers, and they played a significant role in enhancing freedom of press and raising the awareness of the public . Kurdish journalism also experienced a revival during the monarchy rule. However , after the revolution of 1958, it lost ground in terms of freedom,quality and quantity as journalism had in the rest of Iraq.By early 1960s the state of Iraq began to ban Kurdish newspapers from publication.